Preparation of Milk for Reprocessing - Ismatova Mokhinur Sayitniyoz kizi, (American Journal of Biology and Natural Sciences, 2025)
This article evaluates the nutritional components and auxiliary materials of each batch of natural dairy products brought into production in accordance with the regulatory and technical documents for these products. The main attention is paid to the correct determination of the acidity and density of milk and cream sent for condensation and drying.